Promoting sexual health in schools: a systematic review of the European evidence - Ronja Abrams; Johanna Nordmyr; Anna K. Forsman (Frontiers in Public Health, 2023)
IntroductionSexual ill-health is an urgent public health issue with subsequent social and economic costs. There is, therefore, a need for more effective sexual health promotion interventions in an early stage of life. Previous research has focused on preventive sexual health interventions applying a risk perspective, and the limited and scattered evidence concerning school-based sexual health promotion interventions employing a health-resource perspective has not been compiled and synthesized. Hence, this study aimed to systematically review the current evidence on the effects of sexual health promotion interventions conducted in schools in Europe.MethodA systematic review based on the JBI and PRISMA standards was performed, encompassing searches in seven databases to identify sexual health promotion interventions conducted in European schools between 2012 and 2022. Data coding was performed according to a predetermined protocol and included information on study characteristics, intervention content, methods, and outcomes relevant to the current review. A narrative synthesis of the included studies was performed, highlighting the collective results.ResultSeventeen records were included in the review, reporting on 16 individual studies conducted in 7 European countries. Of the 16 included studies, 13 had a quantitative research design, and three had a qualitative design. All three studies with a qualitative research design described positive effects experienced by the participants. Six of thirteen quantitative studies showed statistically significant positive effects on at least one of the outcomes of interest. The outcomes of interest were grouped into five areas, and most studies focused on the area of attitudes toward sexual health.ConclusionThe findings indicate promising evidence of effect for interventions with a health promotion approach, highlighting the importance of strengthening sexual health resources related to respect, communication skills, attitudes, and other positive psycho-social aspects of sexual health. Most sexual health promotion intervention studies have focused on sexual health resource outcomes connected to attitudes and skills, whereas a comprehensive focus on the multi-dimensional sexual health literacy concept is less common and can be recommended to be included in future intervention research.